Solving Research Tasks Using Phenom Prox Desktop Scanning Electron Microscope - Vertsanova, O.V. (Science and Innovation, 2024)
Phenom ProX is a modern effective versatile desktop scanning electron microscope with integrated EDS system. Thanks to its unique design it has a wide scope of application, including material science research, quality management, forensics, pharmaceutical industry, and education.